Transcranial Direct Current Stimulation to Improve the Dysfunction of Descending Pain Modulatory System Related to Opioids in Chronic Non-cancer Pain: An Integrative Review of Neurobiology and Meta-Analysis - Zortea, Maxciel; Ramalho, Leticia; Alves, Rael Lopes; Alves, Camila Fernanda da Silveira; Braulio, Gilberto; Torres, Iraci Lucena da Silva; Fregni, Felipe; Caumo, Wolnei (Frontiers in Neuroscience, 2019)
Background: Opioid long-term therapy can produce tolerance, opioid-induced hyperalgesia (OIH), and it induces dysfunction in pain descending pain inhibitory system (DPIS). Objectives: This integrative review with meta-analysis aimed: (i) To discuss the potential mechanisms involved in analgesic tolerance and opioid-induced hyperalgesia (OIH). (ii) To examine how the opioid can affect the function of DPIS. (ii) To show evidence about the tDCS as an approach to treat acute and chronic pain. (iii) To discuss the effect of tDCS on DPIS and how it can counter-regulate the OIH. (iv) To draw perspectives for the future about the tDCS effects as an approach to improve the dysfunction in the DPIS in chronic non-cancer pain. Methods: Relevant published randomized clinical trials (RCT) comparing active (irrespective of the stimulation protocol) to sham tDCS for treating chronic non-cancer pain were identified, and risk of bias was assessed. tDCS protocols accepted were application in areas of the primary motor cortex (M1), dorsolateral prefrontal cortex (DLPFC) or occipital region. The primary outcome: pain intensity on Visual Analogue-Scale (0-10). Results: Fifty-nine studies were fully reviewed, and 24 with moderate to the high-quality methodology were included. tDCS improved chronic pain with a moderate effect size [pooled standardized mean difference; -0.66; 95% confidence interval (CI) -0.91 to -0.41]. On average, active protocols led to 27.26% less pain at the end of treatment compared to sham [95% CI; 15.89% to 32.90%]. Protocol varied in terms of anodal or cathodal stimulation, areas of stimulation (M1 and DLPFC the most common), number of sessions (from 5 to 20) and current intensity (from 1mA to 2mA). The time of application was 20 min in 92% of protocols. Conclusion: In comparison with sham stimulation, tDCS demonstrated a superior effect in reducing pain in chronic pain conditions. They give perspectives that the top-down neuromodulator effects of tDCS are a promising approach to improve management in refractory chronic not-cancer related pain and to enhance dysfunctional neuronal circuitries involved in the DPIS and other pain dimensions and improve pain control with a therapeutic opioid-free. However, further studies are needed to determine individualized protocols according to a biopsychosocial perspective.